You flip the inequality.
Example: if x > -y and you divide both sides by (-1) then you flip the inequality so: -x < y
Answer:
[three sixths] are the same amount as [one half]
Step-by-step explanation:
Call these units thirds. Split these units in half so there are twice as many. Call these units sixths because six of them make one.
Answer:
x = √(-1) = i
Since the value of √(-1) is not real.
The system has no real solution.
Step-by-step explanation:
The solution to the system of equations is at the point where they intercept each other.
y1 = y2
For the given equation;
y=x^2-2x and y=-2x-1
To get the where they intercept, we will equal both equations;
y=x^2-2x = -2x-1
x^2 - 2x = -2x - 1
x^2 - 2x + 2x + 1 =0
x^2 +1 = 0
x^2 = -1
x = √(-1) = i
Since the value of √(-1) is not real.
The system has no real solution.
The function is increasing on the intervals
x ∈ (-∞, -1) ∪ (1, ∞)